(untitled) (Al-Insyirah Midwifery: Jurnal Ilmu Kebidanan (Journal of Midwifery Sciences), 2025)
Poor vulvar hygiene contributes to the prevalence of reproductive disorders among women. As many as 5.2 million adolescent girls suffer from postmenstrual symptoms due to not maintaining vulvar hygiene during menstruation. This increase is associated with a lack of understanding of adolescent girls about vulvar hygiene. The purpose of this study was to see whether health education about menstrual hygiene using ICM media can improve the knowledge of adolescent girls at SMP IT Al Madinah Nogosari. This study was designed with a quasi-experimental, non-equivalent control group design in the pre-test and post-test. The experimental group received health education about menstrual hygiene using ICM media, while the control group received education through lectures. The subjects of this study were female students at SMP IT Al Madinah Nogosari consisting of 9 classes and a total of 247 students. Using a proportional stratified sampling technique, 39 female adolescents were selected for each group (a total of 78 people). The level of knowledge of adolescent girls was assessed using a questionnaire containing statements about menstrual hygiene. The nonparametric Mann Whitney approach was used to evaluate the data. The research findings show that health education on menstrual hygiene using ICM media on the level of knowledge of female adolescents in the experimental group had a significant impact (p = 0.000) compared to providing health education through lectures in the control group.